Study on Fracture Morphological Characteristics of Refracturing for Longmaxi Shale Formation. (4th March 2020) - Guo, Yintong; Wang, Lei; Chang, Xin; Zhou, Jun; Zhang, Xiaoyu
Abstract : Refracturing technology has become an important means for the regeneration of old wells reconstruction. It is of great significance to understand the formation mechanism of hydraulic fracturing fracture for the design of hydraulic fracturing. In order to accurately evaluate and improve fracturing volume after refracturing, it is necessary to understand the mechanism of refracturing fracture in shale formation. In this paper, a true triaxial refracturing test method was established. A series of large-scale true triaxial fracturing experiments were carried out to characterize the refracturing fracture initiation and propagation. The results show that for shale reservoirs with weak bedding planes and natural fractures, hydraulic fracturing can not only form the main fracturing fracture, which is perpendicular to horizontal minimum principal stress, but it can also open weak bedding plane or natural fractures. The characteristics of fracturing pump curve indicated that the evolution of fracturing fractures, including initiation and propagation and communication of multiple fractures. The violent fluctuation of fracturing pump pressure curve indicates that the sample has undergone multiple fracturing fractures. The result of refracturing shows that initial fracturing fracture channels can be effectively closed by temporary plugging. The refracturing breakdown pressure is generally slightly higher than that of initial fracturing. After temporary plugging, under the influence of stress induced by the initial fracturing fracture, the propagation path of the refracturing fracture is deviated. When the new fracturing fracture communicates with the initial fracturing fracture, the original fracturing fracture can continue to expand and extend, increasing the range of the fracturing modifications. The refracturing test results was shown that for shale reservoir with simple initial fracturing fractures, the complexity fracturing fracture can be increased by refracturing after temporary plugging initial fractures. The effect of refracturing is not obvious for the reservoir with complex initial fracturing fractures. This research results can provide a reliable basis for optimizing refracturing design in shale gas reservoir.